2017
DOI: 10.3390/ijerph14091077
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s IPV, Child Maltreatment Type and the Presence of PTSD in Children and Adolescents

Abstract: This correlational cross-sectional study was designed to investigate whether the intimate partner violence (IPV) suffered by mothers (physical and psychological maltreatment), child eyewitness of psychological and physical maltreatment suffered by the mother, the neglect suffered by children, and the maltreatment (physical and psychological) directly suffered by children are statistically associated to post-traumatic stress disorder (PTSD) symptoms exhibited by the child. In addition, the prevalence of child P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
3
14
0
2
Order By: Relevance
“…In addition, trauma symptoms appear to be an important explanation for the link [48]. Childhood maltreatment may cause a range of internalizing problems in childhood and cause trauma symptoms by distorting the child’s concept of self and others, world view, or affective capacities, making victims vulnerable to RSBs during adolescence or adulthood [9,49,50]. Evidence shows shame, feelings of betrayal or powerlessness components of trauma symptoms in individuals experiencing CEA and CSA may reduce awareness of protective behaviors, in particular contraceptive use [51,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trauma symptoms appear to be an important explanation for the link [48]. Childhood maltreatment may cause a range of internalizing problems in childhood and cause trauma symptoms by distorting the child’s concept of self and others, world view, or affective capacities, making victims vulnerable to RSBs during adolescence or adulthood [9,49,50]. Evidence shows shame, feelings of betrayal or powerlessness components of trauma symptoms in individuals experiencing CEA and CSA may reduce awareness of protective behaviors, in particular contraceptive use [51,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that adverse childhood experiences (ACEs, including forms of child maltreatment and household dysfunctions) are major risk factors for acute and chronic somatic and mental diseases such as anxiety or post-traumatic disorders mediated by risk behaviors such as smoking, alcohol and drug abuse, suicide attempts, aggressive behaviors, risky sexual behaviors, and low mental resilience [12,13,14,15,16,17,18,19,20]. Previous studies provided strong evidence that ACEs tend to co-occur in which intergenerational transmission of adversity might be a contributing factor [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…У тех лиц, кто перенес особо тяжелые формы насилия или отделение от семьи и бездомность, чаще формируется посттравматический стрессовый синдром. Возникающие в рамках посттравматического стрессового расстройства тягостные навязчивые воспоминания способствуют использованию ПАВ с целью самолечения как попытки избежать эти воспоминания [20][21][22].…”
Section: жестокое обращение в детстве и употребление павunclassified